Overview of Malaysian standards on alloy steels - Maleque, Md. Abdul (2017)
Malaysian standards (MS) on alloy steels are developed to ensure that alloy steel products use in Malaysia, whether it is imported or locally manufactured, complied to the same minimum quality. The Standards to be adopted for Malaysian Standards are universal; commonly in use for the industries worldwide. So far there is no proper regulation on alloy steels products but with time it is expected that the developed Malaysian Standards will be referred to Customs Act and become mandatory standards. Technical Committee on Alloy Steels is number 4 (known as TC4) and one of the 24 standards sectors to reflect the country’s market need. These are formed by DSM to develop various types of national standards or adopt international standards. An overview on the process flow of MS development has been presented followed by the case examples on the details of developed MS and review process for the maintenance of MS on alloy steel. This talk also provides a platform for info sharing and discussion on matters relevant to alloy steels.